Implementation of Law Number 14 of 2008 on Public Information Transparency in the Indonesian House of Representatives (DPR RI) - Feri Firdaus; Zaimasuri Zaimasuri (Dynamics of Politics and Democracy, 2024)
Purpose: The House of Representatives of the Republic of Indonesia (DPR-RI) is mandated to represent the people's voice through general elections. This role becomes meaningful when DPR ensures transparency by providing public access to information. However, its commitment to information disclosure is questionable, especially after limited public access to documents related to the KPK Law revision, Omnibus Law, and the Job Creation Bill. This study analyzes the implementation of public information disclosure policies within the DPR-RI. Methodology: This study uses a descriptive qualitative method. Primary and secondary data were obtained through in-depth interviews with key informants and literature studies related to the topic. Result: The research shows that the implementation of the Public Information Disclosure Law in the DPR-RI is not yet optimal. This is particularly seen in the underutilization of media channels and poor management of information sources. Conclusion: The ineffectiveness of public information disclosure implementation in DPR-RI stems from limited use of digital media, weak performance of the Information and Documentation Management Officer (PPID), and lack of institutional commitment. These factors obstruct transparency and accountability in a democratic legislative institution. Limitation: This study is limited to evaluating the DPR-RI and does not include a comparative assessment with other government institutions or legislative bodies. Contribution: This research contributes to the theoretical and practical understanding of public information policy implementation in legislative institutions as part of communication policy studies.